Impact of Electronic Payment System on the Profitability of Nepalese Commercial Banks - Basnet, Sanila (Nepalese Journal of Finance, 2024)
This study examines the impact of electronic payment system on the profitability of Nepalese commercial banks. Return on assets (ROA) and return on equity (ROE) are the selected dependent variables. The selected independent variables are mobile banking, quick response code payment, automated teller machine, digital wallet, credit cards and point of sales. The study is based on primary and secondary data of 8 commercial banks with 130 respondents. To achieve the purpose of the study, structured questionnaire is prepared. Secondary data were collected from Banking and Financial Statistics published by Nepal Rastra Bank and annual reports of the selected commercial banks. The correlation coefficients and regression models are estimated to test the significance and importance of electronic payment system on the profitability of Nepalese commercial banks. The study showed that mobile banking has a positive relationship with return on assets and return on equity. It indicates that better the mobile banking services provided by banks, higher would be the return on assets and return on equity. Similarly, QR payment has a positive relationship with return on assets and return on equity. It indicates that more the payment through QR payment services, higher would be the return on assets and return on equity. Likewise, ATM banking has a positive relationship with return on assets and return on equity. It indicates that better the ATM services provided by the banks, higher would be the return on assets and return on equity. Further, digital wallet has a positive relationship with return on assets and return on equity. It indicates that higher the practices of digital wallet banking, higher would be the return on assets and return on equity. In addition, credit card has a positive relationship with return on assets and return on equity. It indicates that higher the number of payments through credit card, higher would be the return on assets and return on equity. Moreover, POS banking has a positive relationship with return on assets and return on equity. It indicates that practice of point of sales banking leads to increase in return on assets and return on equity.